Interleukin-6 blockade for prophylaxis and management of immune-related adverse events in cancer immunotherapy - Dimitriou, Florentia; Hogan, Sabrina; Menzies, Alexander M.; Dummer, Reinhard; Long, Georgina V. (European journal of cancer (1990), 2021)
Immune checkpoint inhibitors (ICIs) have activity across many tumor types, but activation of the immune system may also lead to significant, often steroid-refractory immune-related adverse events (irAEs). We sought to determine the activity of tocilizumab, an anti-interleukin-6 receptor monoclonal antibody, in treatment or prevention of auto-immune irAE in ICI-treated patients. Institutional databases from 2 melanoma centers were reviewed for patients treated with ICIs and tocilizumab. Longitudinal assessment of C-reactive protein (CRP) and assessment of clinical improvement or prevention of flare of pre-existing auto-immune conditions were utilised to evaluate the benefit of tocilizumab. Twenty-two patients were identified. Two were treated prophylactically. Twenty were treated for management of irAEs. Median time to irAE onset from ICI start was 48 days (range 8–786) and from irAE onset to tocilizumab 32 days (range 1–192). Median time to irAE resolution from tocilizumab was 6.5 days (range 1–93). Clinical improvement/benefit was demonstrated in 21/22 patients. Median CRP prior to ICI administration was 32 mg/l (range 0.3–99), at the onset of irAE 49.5 mg/L (range 0.3–251, P = 0.047) and after tocilizumab 18 mg/L (range 0.3–18, P = 0.0011). Tocilizumab was well tolerated with self-limiting and transient toxicities in 11 (50%) patients. From start of ICI, median progression-free survival was 6 months (range 3.9–18.8) and median overall survival was not reached. Tocilizumab was a well-tolerated and effective steroid-sparing treatment for both management of irAEs, as well as prevention of flare of pre-existing auto-immune disorders. Prospective trials to evaluate its efficacy and impact on cancer outcomes compared with standard strategies are required. •Anti-IL6 (interleukin-6) was effective for management of immunotherapy-related toxicities.•In pre-existing auto-immune disorders, anti-IL6 could prevent flare during immune checkpoint inhibitor.•Clinical improvement/benefit was demonstrated in 21/22 patients (96%).•Anti-IL6 was well-tolerated in 21 patients, with transient toxicities in 50%.•Caution is required in patients with underlying bowel disease (bowel perforation).